Associations between fear of COVID-19 and mental health in Ghana: A sequential mediation model - Jiajia Ye; Po-Ching Huang; Emma Sethina Adjaottor; Frimpong-Manso Addo; Mark D. Griffiths; Daniel Kwasi Ahorsu; Chung-Ying Lin (Heliyon)
Introduction: Although the coronavirus disease 2019 (COVID-19) pandemic has ceased globally, individuals may still suffer from various psychological burdens in the post-COVID-19 era. The present observational cross-sectional study investigated how fear of COVID-19 can affect mental health through mediators including stress, perceived stigma, and preventive behaviors among young adults in Ghana. Methods: A total of 635 participants aged between 18 and 29 years (mean age = 20.2 years [SD = 2.04]) were recruited to complete measures of COVID-19 fear, stress, perceived stigma, preventive behaviors, and mental health status from June to August 2022. Results: Results from structural equation modeling found that (i) fear of COVID-19 was associated with stress and perceived stigma (standardized coefficients [βs] = 0.518 and 0.148, p-values < 0.001), (ii) stress and perceived stigma were associated with frequency of preventive behaviors (β = 0.173, p < 0.001 for stress; −0.100, p < 0.05 for perceived stigma), and (iii) preventive behaviors were associated with mental health status (β = 0.118, p < 0.01). Stress and preventive behavior (β = 0.009, 95%CI: 0.000, 0.003) and perceived stigma and preventive behavior (β = −0.007, 95%CI: −0.283, −0.020) were significant mediators in the association between fear of COVID-19 and mental health. Discussion: The findings suggest that fear of COVID-19 may affect mental health through multiple pathways. Health professionals should provide comprehensive mental health interventions that address various influences regarding fear of COVID-19. Further research that examines the relationships between COVID-19-related variables and various health conditions is needed in the post-COVID-19 era to help develop different preventive and therapy measures.